Adherence to national exercise guidelines by patients attending emergency departments: A multi‐site survey. (20th March 2017) - Berlingeri, Paul; Cunningham, Neil; Taylor, David McD; Knott, Jonathan; McLean, Daniel; Gavan, Rex; Plant, Luke; Chen, Hayley; Weiland, Tracey
Abstract: Objective: The proportion of adults in Australia meeting or exceeding the national guidelines for physical activity has remained relatively static over the past 10 years. The research objective was to measure self‐reported physical activity and sedentary behaviour among ED patients in accordance with Australia's current physical activity and sedentary behaviour guidelines, revised in 2014. Methods: A convenience sample of participants was recruited from three EDs in Melbourne between February and May 2016. Eligible participants were administered the International Physical Activity Questionnaire – Short Form plus researcher‐derived questions. Participants were assessed as whether meeting the physical activity guidelines or not, using pre‐defined criteria. Results: The proportion of 18–64 year olds meeting all of the physical activity guidelines was 19.0% (95% confidence interval [CI] 15.2–22.8). A majority of participants (63.1%, 95% CI 58.5–67.7) met the aerobic component of the guidelines although only 28.9% (95% CI 24.5–33.3) of participants reported undertaking strength building exercises two or more times per week. Adults in the oldest age group were found to be less likely to engage in muscle strengthening exercises (23.3%, n = 30) than those in the youngest age group (40.0%, n = 60, P = 0.005). Average daily sitting time (minutes) did not differ between men (median = 300) and women (median = 360, P = 0.118). Conclusions: Overall adherence with physical activity guidelines is low among adults attending the ED. All adults need to be encouraged to undertake muscle strengthening activities, especially adults in older age groups.